How Should I Start Research in Cyber Security? Suggestions for Researchers According to Bibliometric Analysis Data - Aslihan İstanbullu (Sakarya University Journal of Education)
The aim of this study is to discover the research trends in the field of cyber security with performance analysis and to reveal the intellectual structure of the field of cyber security with scientific mapping. For this purpose, articles published in the field of cyber security between 1998-2021 in the WoS database were examined. The research was carried out in accordance with the bibliometric analysis guide. In the data collection phase, 1,631 articles were included in the study by taking into account the criteria determined among 15,781 studies using the PRISMA procedure. R program was used in bibliometric analysis. According to the findings of the study, there has been a significant increase in article productivity in the field of cyber security after 2020. Although IEEE Access is the journal with the highest number of publications in the field, IEEE Transactions on Smart Grid ranks first according to h-index and g-index values. Considering the topics studied according to the years, it is seen that in the first years, issues related to the law such as cybercrime and cyber terrorism were examined, and recently, in addition to these, current technological issues have been included. It is observed that the most effective publication is 'The Internet of Things for Health Care: a Comprehensive Survey' by Islam et al. which examines the security of the Internet of Things in health care, which is also a current issue.